Pemberian MP-ASI Dini dengan Kejadian Stunting pada Balita di Desa “TJ” Wilayah PKM “M” Lebak – Banten - Dini Rostianti Putri; Roslina Roslina (Jurnal Obstretika Scientia, 2020)
Malnutrition at an early age increases infant and child mortality, causes suffering, is easy to get sick and has poor posture as adults (Millennium Challenge Account Indonesia, 2018). The incidence of short toddlers or commonly referred to as stunting is one of the nutritional problems experienced by toddlers in the world today. In 2017, 22.2% or around 150.8 million children under five in the world were stunted. The average prevalence of stunting under five in Indonesia in 2005-2017 was 36.4% (Kemenkes RI, 2018). The purpose of this study was to determine the relationship between early complementary feeding and the incidence of stunting in children under five in the "TJ" Village, the Working Area of the "M" Health Center Lebak - Banten. . This research was conducted with a case control design. Data collection was carried out directly using a questionnaire on the early MP-ASI variable and the Stunting variable was obtained from the register book owned by the cadres. From the results of this study, the value of P = 1,000, which means that there is no significant relationship between the provision of early complementary feeding and the incidence of stunting, and the value of OR = 1, which means that toddlers who are given early complementary feeding or not have the same risk of experiencing this event. stunting. Therefore, it is very important to increase public awareness about meeting the nutritional needs of 1000 HPK.